An expanded training program for endosonographers improved self-diagnosed accuracy of endoscopic ultrasound-guided fine-needle aspiration cytology of the pancreas. (September 2014) - Harada, Ryo; Kato, Hironari; Fushimi, Soichiro; Iwamuro, Masaya; Inoue, Hirofumi; Muro, Shinichiro; Sakakihara, Ichiro; Noma, Yasuhiro; Yamamoto, Naoki; Horiguchi, Shigeru; Tsutsumi, Koichiro; Okada, Hiroyuki; et al.
Abstract Objective. Rapid on-site evaluation (ROSE) of cytologic adequacy improves the diagnostic yield of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). However, on-site advice from a cytotechnologist or cytopathologist is not always available during EUS-FNA. To enhance endosonographers' ability to assess the adequacy of EUS-FNA specimens, we designed an intensive, 2-h interactive training program. The aim of this study was to determine the usefulness of the program. Methods. Four cytological pictures were selected by a trained cytotechnologist and board-certified cytopathologist from each of the seven patients who underwent EUS-FNA for pancreatic mass in Okayama University Hospital. In total, 28 pictures were used in this study. Twenty endosonographers and 14 cytologists with different levels of EUS-FNA experience evaluated cytological pictures independently before and after the training program. Results. Endosonographers' skill in evaluating the adequacy of EUS-FNA specimens was significantly improved after the completion of the training program (p < 0.001). In contrast, almost all cytologists correctly judged the adequacy of the specimens before taking the training program. Conclusions. This intensive, 2-h interactive training program is useful for endosonographers and capable of improving ROSE of EUS-FNA specimens.